Undergraduate Students’ Reading Interest and Reading Comprehension Achievement in a State Islamic University - RUMAINAH RUMAINAH (Ta'dib: Jurnal Pendidikan Islam, 2018)
This research was aimed to describe the relationship between reading interest and reading comprehension achievement of EFL students at UIN Raden Fatah Palembang in the academic year 2013-2016. Quantitative method, especially correlational study, was used. The population of the study was 466 active EFL students. By using purposive sampling technique, there were 86 students involved as participants in this research. The data were obtained by using two instruments which were reading interest questionnaire and reading comprehension test. Pearson Product Moment Correlation Coefficient was used to analyze the data. From the result of the data analysis, it was found that there was no significant correlation between students’ reading interest and their reading comprehension achievement since the p-value was (.887) greater than significance value (.887 > .005). In short, reading interest did not have any relation to reading comprehension achievement of undergraduate EFL students of UIN Raden Fatah Palembang.